Respostas

2014-02-27T11:16:07-03:00
A)    1 =   1 .√3  =    √3     =  √3      
     √3     √3.√3        √9          3


b)  5   =   5 .√2  =  5√2   =  5√2
   √2      √2 .√2      √4          2

c)     1      =         1       . ( √5 - 2)    =            √5 -2                      = √5 - 2 = √5 - 2
    (√5 + 2 )      (√5 + 2 ) . (√5 - 2)          √25 - 2√5 + 2√5 - 4              5 - 4

d)    √2         =         √2   . ( √2 - √3) =      √4  - √6          =    2 - √6 =  (2 - √6)    =
    (√2 + √3)      (√2 + √3) · (√2 - √3)      √4 - √6 +√6 -√9        2 - 3        - 1

=  - (2 -√6)  = - 2 +√6

1 1 1